Efeito do extrato de Uncaria tomentosa (Wild.) D.C. na hidrólise de nucleotídeos de adenina em linfócitos de ratos submetidos a modelo experimental de artrite reumatóide - Castilhos, Lívia Gelain (2012)
The extracts of stem and root of the Uncaria tomentosa plant present several properties. Among them, the anti-inflammatory property is very important since it has been studied and widely observed in cases of rheumatoid arthritis (RA) treatment. The model of arthritis induced by complete Freund s adjuvant (CFA) in rats is a model widely used in searches for new therapies for chronic inflammatory arthropathies, such as RA, which in turn, is a chronic inflammatory disease, immune-mediated and with rather complex physiopathology. During the inflammatory process, a complex and hierarchical cytokines network rules this process triggering a Th1 type immune response. Among the mediators that modulate the action of lymphocytes during inflammatory process, we emphasize ATP, ADP, AMP and the nucleoside adenosine, which are essentials to the initiation and maintenance of inflammatory responses. The effects of these molecules are promoted by the action of specific purinergic receptors and controlled by an enzyme complex on the cell surface. The objective of this study was to evaluate the effect of the Uncaria tomentosa extract on the metabolism of adenine nucleotides through the activity of ectoenzymes involved in the ATP metabolism in lymphocytes of rats submitted to an experimental model of rheumatoid arthritis.The animals were divided into four groups, namely, control (C), extract (E), arthritis (AR) and arthritis associated with extract (AR+E). Fifteen days after AR induction by CFA, the U. tomentosa dry extract was administered two times a day at the dose of 150mg/kg for 45 days. After treatment, the blood was collected by cardiac puncture and the lymphocytes were isolated to E-NTPDase and ADA activity determination, and the serum used to purine level measurement. Results show an increase in the E-NTPDase activity in rats with CFA induced arthritis compared to control. Rats treated only with Uncaria tomentosa extract showed E-NTPDase and E-ADA activity maintained in basal levels. In rats with RA treated with Uncaria tomentosa, the extract was able to prevent the increase on the E-NTPDase activity, although the ATP and adenosine levels were decreased and ADP levels were increased in extracellular medium. The increase in E-NTPDase activity might be related to the attempt to maintain basal levels of ATP and ADP in basal levels in the extracellular medium, since the RA induction causes tissue damage and consequently large amounts of ATP in the cell. This way, the Uncaria tomentosa extract was able to prevent the increase in the E-NTPDase activity promoting RA induction.